2023
DOI: 10.3390/cryst13010133
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Synthesis of rGO-ZnO/CuO Nanocomposites for Photocatalytic Degradation of Organic Pollutants

Abstract: Nanomaterial-based catalytic conversion of hazardous organic pollutants into benign substances is one of the green methods employed for wastewater treatment. This study demonstrates the fabrication of (rGO-ZnO)/CuO nanocomposites (NCs) via a microwave (MW)-assisted method for (photo)catalytic application. The crystal structure, optical, morphological, and electrochemical characteristics were examined using X-ray diffraction (XRD), spectroscopic, microscopic, and electrochemical techniques. The analysis indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…From Figure 2c–e, as it can be seen in the spectrum of the Ag–CuO/GO composite (Ag 1%, 5%, and 10%) that the peak at 628 cm −1 is attributed to vibrations associated with the CuO bond during stretching. Furthermore, it can be observed that the addition of Ag with various ratios, that is, 1%, 5%, and 10%, significantly reduced the stretching intensity of OH and increased the peak transmittance of the composite, confirming higher light absorption due to surface plasmon resonance 36–38 …”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…From Figure 2c–e, as it can be seen in the spectrum of the Ag–CuO/GO composite (Ag 1%, 5%, and 10%) that the peak at 628 cm −1 is attributed to vibrations associated with the CuO bond during stretching. Furthermore, it can be observed that the addition of Ag with various ratios, that is, 1%, 5%, and 10%, significantly reduced the stretching intensity of OH and increased the peak transmittance of the composite, confirming higher light absorption due to surface plasmon resonance 36–38 …”
Section: Resultsmentioning
confidence: 88%
“…These figures show that at some locations rGO and CuO with Ag were mixed properly and form sheets of composites with fibrillary structures that were tightly stacked while at other locations they were arranged haphazardly, which may result from the breakage or exfoliation of larger sheets. Overall, the SEM images show that all three components were mixed efficiently, which enhance the performance activity of catalyst 38,44–48 …”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Multiple studies have been reported on ZnO combinational catalysts such as NiS/ZnO 23 , CuO/ZnO 24 , Ni/rGO 25 , Ag/ZnO 26 28 , ZnO 29 , graphene-ZnO 30 , 31 , Co–ZnO 32 for the PNP reduction reaction. Recently, Bekru et al, reported the (rGO–ZnO)/CuO nanocomposite interface is a highly efficient photo-catalyst for PNP reduction 33 . Reduced graphene oxide and semiconductor based composite exhibit increased photocatalytic performance than pure oxide nanostructure 34 .…”
Section: Introductionmentioning
confidence: 99%